2014
DOI: 10.1159/000362990
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Role of Sphingosine 1-Phosphate on Insulin Resistance

Abstract: Insulin resistance is a complex metabolic disorder in which insulin-sensitive tissues fail to respond to the physiological action of insulin. There is a strong correlation of insulin resistance and the development of type 2 diabetes both reaching epidemic proportions. Dysfunctional lipid metabolism is a hallmark of insulin resistance and a risk factor for several cardiovascular and metabolic disorders. Numerous studies in humans and rodents have shown that insulin resistance is associated with elevations of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 84 publications
(103 reference statements)
0
48
0
Order By: Relevance
“…In the case of trained athletes, however, this does not seem to be true, because in these individuals, the increased lipid content is accompanied by well-preserved insulin responsiveness [21]. For these reasons, most authors highlight the intermediate lipid metabolites, mainly DAG and CER, but not simple myocyte lipid overload as a probable direct cause of insulin resistance [7,8,22]. …”
Section: The Lipid-centric View Of Insulin Resistancementioning
confidence: 99%
“…In the case of trained athletes, however, this does not seem to be true, because in these individuals, the increased lipid content is accompanied by well-preserved insulin responsiveness [21]. For these reasons, most authors highlight the intermediate lipid metabolites, mainly DAG and CER, but not simple myocyte lipid overload as a probable direct cause of insulin resistance [7,8,22]. …”
Section: The Lipid-centric View Of Insulin Resistancementioning
confidence: 99%
“…It has been found that LCACoAs and DAGs affect insulin signaling pathway through the activation of serine/threonine PKC isoenzymes [12], whereas Cer inhibits the pathway at Akt/PKB level [13]. Other sphingolipid species such as gangliosides [14] or sphingosine-1-phosphate [15] may also contribute to IR.…”
Section: Introductionmentioning
confidence: 99%
“…The precursor ions of S1P (m/z 380.3) and D7-S1P (m/z 387.3) were cleaved into the fragment ions of m/z 264.3 and m/z 271.3 respectively. Ceramides were extracted and quantified as recently described [14]. Briefly, lipid extraction was performed using C17-ceramide as internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…Once generated, ceramides can be further metabolized to the bioactive metabolite sphingosine 1-phosphate (S1P). S1P can be released via specific ATPbinding cassette (ABC)-transporters or via the S1P transporter spinster homolog 2 into the extracellular environment and activates 5 specific G protein-coupled S1P receptors (S1P [1][2][3][4][5] ) in an auto-and paracrine manner [14,15]. In addition to well established effects of S1P in pathogenesis of metabolic diseases, a growing body of evidence indicates that S1P can be considered as an important regulator of fibrosis [16,17].…”
Section: Introductionmentioning
confidence: 99%